A Study on Leaching Properties of End-of-Life Tire for Urban Use Applications - Kus Sahin, Candan; Coskun, Sezen (European Journal of Applied Sciences, 2022)
Urban runoff or the flow of rainwater in urban areas, can carry leachate chemicals, released from End-of-Life Tire (ELT), may be a toxicity source to public. These matters can impact on living organisms contact to water which can be harmful. Because ELTs very often utilized in urban open space applications, it was aimed to investigate water leachates comparatively from two different inner side parts which one is punctured and patched with rubber cement adhesive (A) and other is normal non-patched (B). In these regards, leachate dependence between these two different parts were evaluated with using selected physicochemical properties of water. However, except pH, all other measured parameters appear to higher for rubber cement adhesive patched sample (B) rather than sample A. These could be expected, considering the heterogeneous rubber part which patched with rubber cement adhesive could be affects further leachates to water. It is important to note that a positive correlation was observed for parameters and duration for both experimental measurements. The highest EC value of 1425 μs/cm, TDS of 1004 ppm, salinity of 0.73 ppt and Turbidity value of 9.3 NTU were found after maximum (14 days) water leaching duration for sample. The similar trend was also realized for sample B that the highest EC value of 2333 μs/cm, TDS of 1670 ppm, salinity of 1.18 ppt and turbidity value of 19 NTU were found after 14 days of water leaching.